A NEW METHOD OF SYNTHESIS OF COENZYME Q10 FROM ISOLATED SOLANESOL FROM TOBACCO WASTE - Atla, Srinivasa Rao; Raja, Bhavani; Dontamsetti, Basava Raju (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Development of new semi-synthetic route for Coenzyme Q10 from solanesol isolated from tobacco waste and structural characterization by FT-IR, 1H & [13]C NMR, LC-MS spectral data and elemental analyses. Methods: The authors described herein a new, short and highly efficient semi-synthetic route for Coenzyme Q10 (Scheme 1,2&3) starting with isolated solanesol (I) from tobacco waste via the formation of solanesol chloride (II), solanesol ester (III), solanesol acetone (IV) and isodecaprenol (V) as an intermediates. Later attachment of two subsections of the target, that is, a benzohydroquinone as an important precursor (VII), and an isodecaprenol (V, 50 carbon chain) was anticipated to occur via a zinc chloride catalyzed coupling reaction obtained Coenzyme Q10 (VI) in 90.00 % isolated yield. The synthesized compounds were characterized by FT-IR, 1H & [13]C NMR, LC-MS spectral data and elemental analyses. Results: Coenzyme Q10 has been semi-synthesized by a novel process from the solanesol isolated from tobacco waste (biological waste) using readily available and inexpensive precursors like PCl3, ethyl acetoacetate, Grignard reagent and benzohydroquinone derivative via the formation of important precursor Isodecaprenol and optimizing the each reaction. The overall yield of Coenzyme Q10 was 17.24% under the optimized conditions. Conclusion: This process achieved CoQ10 starting from an abundantly available solanesol from tobacco waste. Further improvement in the coupling reaction between Isodecaprenol (V) and Benzohydroquinone (VII) in the presence of Lewis acid may lead to a better and viable synthetic process. Hence this process may be economical and potential to be used for large-scale production.